"This is not Normal": the Role of Lawyer Organizations in Protecting Constitutional Norms and Values - Leslie C. Levin (Washington University Journal of Law and Policy, 2022)
Lawyer organizations in the United States perform a range of functions. Some are essentially social clubs that provide networking opportunities for lawyers. Others help their members stay up to date on changes in the law and provide other educational and material benefits. Through these efforts, lawyer organizations often serve as a site where lawyers learn the norms and values of the legal profession. Some lawyer organizations also perform more outward facing functions, working through lobbying and litigation to maintain lawyers’ status and protect their economic interests. Others pursue even broader goals, working to enhance the functioning of the courts, provide access to justice, and improve the law. Some of these organizations seek to advocate on a broad range of social issues and advance the rule of law. (As they define that contested term.) But what role do lawyer organizations actually play in protecting constitutional norms and values in the twenty-first century?
Keywords: Lawyer; Organizations; Constitution; Constitutional; Norms; Values; Protecting; Normal; Lawyers; ABA; Social; Interests; Modern; Twenty-first century; Changes; Education; Lobbying; Litigation